Sinus bradycardia as the initial manifestation of multisystem inflammatory syndrome in children. (14th October 2021) - Gonzalez, K; Mendoza Britto, I; Mateu, M; Marcano, E; De Izaguirre, J; Sonshire, F; Falcon, D; Cardenas, A; Ortega, R; Morr, I; Mendoza Mujica, I
Abstract: Background: While cardiovascular complications, including arrhythmias are now a recognized manifestation of Multisystem inflammatory syndrome in children (MIS-C), there are no reports of primary bradycardia preceding the clinical presentation. We sought to describe a case series of sinus bradycardia as an initial manifestation of MIS-C. Methods: We included a series of 10 consecutive patients with confirmed COVID-19 who met WHO and CDC criteria for MIS-C, who developed sinus bradycardia with a heart rate measured in the awake state that was below the normal range for age for children, as an initial manifestation of the disease, in a prospective observational multicenter study. Patients underwent clinical, laboratory evaluation, ECG, Holter, telemetry, echocardiogram, chest X Ray, and a chest CT scan. Results: Of the 10 patients included, 6 were male, with a mean age of 6.52±5.35 years, range 4 months to 14 years. All cases were Hispanic. Bradycardia was transient and did not merit treatment. Coronary abnormalities were noted in 6 cases; 4 patients had mild coronary ectasia; 9 patients had pericardial effusion with no evidence of tamponade. All patients had a mild clinical course; none had shock, heart failure, the need for mechanical ventilation, or died. All blood markers (Troponin, BNP, Platelet count, C-reactive protein, D-dimer, Ferritin) returned to normal levels by discharge/follow-up with a favorable outcome including resolution of coronary dilatation in all but 2 in which aneurysm persisted. Treatment: All patients received steroids and low-weight-molecular heparin 10 patients, 8 aspirin and 8 intravenous immunoglobulins. Conclusion: Sinus bradycardia may be the initial manifestation of MIS-C, usually transient and mild. Physicians should be aware of this presentation. Funding Acknowledgement: Type of funding sources: None.